RIGID-FLEXIBLE COUPLING DYNAMIC MODELING AND LOAD CHARACTERISTICS RESEARCH OF GEAR TRANSMISSION SYSTEM - ZHANG Zheng; FENG GuangBin; SUN HuaGang; HAO ChiYu (Jixie qiangdu, 2020)
Gear transmission system is one of the core components of tracked vehicles. In order to grasp the load characteristics of gears during system operation,this paper built a joint modeling method based on Creo,HyperMesh and RecurDyn software platform based on rigid-flexible coupling dynamics. Based on the time-varying contact force and the flexibility of the gear,the system rigid-flexible coupling simulation model was established and its accuracy was verified by the test bench.Taking a practical working condition as an example,the simulation results of the rigid-flexible coupling model and the rigid body model are compared and analyzed. The results show that the rigid-flexible coupling model can more accurately describe the bearing motion of the gear. According to the variation law of gear stress obtained by simulation,the causes of the interruption of the tooth failure during the system operation are analyzed. The simulation process and results provide a reference and basis for gear fatigue life prediction and system fault diagnosis.